(untitled) (Research, Society and Development, 2021)
The present study aimed to verify whether the financial investments made in a specific way to certain sports modalities provide the country with greater chances of winning medals, diplomas or Olympic participation. The Olympic modalities that had athletes contemplated by the Brazilian Bolsa-Atleta program between 2005 and 2016 were used as a sample. Initially, a survey of the financial resources allocated by modality was carried out, and then the Olympic results obtained in the same section were identified. temporal. For the analysis of the relationships between the financial investments made and the Olympic results, descriptive statistics were performed followed by Spearman’s rho (ρ) statistical test. It can be seen that the referred program distributed the amount of money unevenly among the sports analyzed and only in the last Olympic cycle (2013-2016) was a positive correlation found between the amount invested and the number of participations, diplomas and medals olympic games. It was concluded, therefore, that the investment in the way it is happening does not guarantee greater chances of winning Olympic medals or diplomas.